Perancangan Model TDABC Dalam Menghitung Unit Cost Pendidikan - Tonny Stephanus Eoh (BIP's JURNAL BISNIS PERSPEKTIF, 2018)
Calculation of education unit cost for S1 Economics courses at the University "X" using the TDABC method show that the average tuition fees is Rp. 3,640,469,/student for the academic year 2015/2016; or Rp.1,820,235,-/student for each semester. Meanwhile, the basis for calculating the unit cost of education that is used for now, just following the unit cost of its competitors, amounting to Rp.1.800.000,-/student for each semester. So that the unit cost of education courses calculated by TDABC method and the current method relative did not experience a significant difference. However, the information can be used by management to evaluate the existence of other faculty who use more resources and have fewer number of students.